2022
DOI: 10.1021/acs.jafc.2c02389
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Larch Tannins with Different Mean Polymerization Degrees: Controlled Degradation Based on Hydroxyl Radical Degradation

Abstract: Hydroxyl radical produced by hydrogen peroxide decomposition under UV radiation was used to degrade larch tannins in an environmentally friendly manner. The formaldehyde reactivity of the degraded products was used as an index to control the mean degree of polymerization (mDP) of the degraded products, and the effects of different mDP on the antioxidant activity of tannins were studied. Results showed that hydroxyl radical could significantly reduce the degree of polymerization (DP) and molecular weight (M w )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…The complex structure of tannins gives them a wide range of biological activities, but they are difficult to hydrolyze and absorb by the body. It has been shown that the higher the molecular weight of tannins is, the lower is the bioactivity and bioavailability [46,47]. The anti-nutritional properties of tannins could be reduced by decreasing the tannin polymerization during food fermentation, and the hydrolysis of tannin components by tannases is a feasible method to enhance the digestibility and bioactivity of fermented foods.…”
Section: Tannasementioning
confidence: 99%
“…The complex structure of tannins gives them a wide range of biological activities, but they are difficult to hydrolyze and absorb by the body. It has been shown that the higher the molecular weight of tannins is, the lower is the bioactivity and bioavailability [46,47]. The anti-nutritional properties of tannins could be reduced by decreasing the tannin polymerization during food fermentation, and the hydrolysis of tannin components by tannases is a feasible method to enhance the digestibility and bioactivity of fermented foods.…”
Section: Tannasementioning
confidence: 99%